Effect of a mobile application and smart devices on heart rate variability in diabetic patients with high cardiovascular risk: A sub-study of the LIGHT randomized clinical trial - (:unkn) unknown (POLISH CARDIAC SOC-POLSKIE TOWARZYSTWO KARDIOLOGICZNE, 2021)
Background: This investigation aims to evaluate the effect of a mobile application and smart devices on frequency and time domains of heart rate variability (HRV) in diabetic patients in 1-year follow-up. Methods: This is post-hoc analysis of a diabetic subgroup of Lifestyle Intervention usinG mobile technology in patients with high cardiovascular risk: a pragmatic randomized clinical Trial (LIGHT). One hundred and nine and 118 patients were enrolled in two arms: the intervention plus usual care and the usual care arm. The study outcome was the 1-year HRV parameters adjusted to the baseline HRV parameters. HRV measures were recorded for every patient at the randomization and final visits with 24-hour Holter monitoring. Results: There was an improvement in the standard deviation of normal to normal (SDNN) R-R intervals 24-hour by 4.8 (adjusted treatment effect 4.8, 95% confidence interval [CI], 0.1-9.5; P = 0.044) in the intervention-plus-usual-care arm compared to usual care after a 1-year follow-up. The improvement was also experienced in other HRV time domains including standard deviation of the mean R-R intervals calculated over a 5-minute period, SDNN, square root of the mean squared difference of successive R-R intervals, and the percentage of the differences between adjacent normal R-R intervals exceeding 50 milliseconds. A significant enhancement was also detected in HRV frequency domains of total power low frequency and high frequency in the intervention plus usual care compared to usual care after a 1-year follow-up. Conclusions: The mobile application and smart device technology compared to usual care alone improved HRV parameters in diabetic patients at 1-year follow-up.
Keywords: diabetes mellitus; heart rate variability; mobile application; AUTONOMIC NEUROPATHY; BLOOD-GLUCOSE; INTERVENTION; ASSOCIATION; MORTALITY